2004
DOI: 10.1063/1.1835562
|View full text |Cite|
|
Sign up to set email alerts
|

Underwater electrical explosion of a Cu wire

Abstract: Results and analysis of a microsecond time scale underwater electrical wire explosion are presented. Experiments were carried out with a Cu wire exploded by a current pulse ⩽100kA with microsecond time duration. The analysis is based on shadow and spectrally resolved streak photography which were used to monitor the evolution of the discharge channel and the shock wave. The obtained data were used for hydrodynamic calculation of the generated water flow parameters, such as pressure and flow velocity distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…The main advantages of this approach are related to the large electric filed breakdown value (>300 kV/cm) of water and its low compressibility (adiabatic index c ¼ 7.15), which allows an extremely high energy density deposition into the exploding wire to be achieved. Indeed, recent experimental, analytical and numerical studies [11][12][13][14][15] of underwater electrical wire explosion showed that, using pulsed power generators with a stored energy of only a few kJ, an extreme state of matter, i.e., up to 500 eV/atom and pressure of 5 Â 10 9 Pa can be obtained.…”
mentioning
confidence: 99%
“…The main advantages of this approach are related to the large electric filed breakdown value (>300 kV/cm) of water and its low compressibility (adiabatic index c ¼ 7.15), which allows an extremely high energy density deposition into the exploding wire to be achieved. Indeed, recent experimental, analytical and numerical studies [11][12][13][14][15] of underwater electrical wire explosion showed that, using pulsed power generators with a stored energy of only a few kJ, an extreme state of matter, i.e., up to 500 eV/atom and pressure of 5 Â 10 9 Pa can be obtained.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] The edition work of Chace and Moore 6 and the work of Lebedev 7 constitute very good and extensive reviews of EW. From the beginning, electrical signals, [8][9][10] shock wave imaging, 11,12 and radiation measurement 13 were the primary tools to understand the phenomena. Because the shock wave generated has rich information about the shock wave generator system, different wire materials, dimensions, and surrounding media were studied in the past.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum wire heating rate considered in calculations was similar to that obtained in the electrical wire explosion experiments in Refs. [12][13][14] .…”
Section: The Model and Calculation Resultsmentioning
confidence: 98%
“…8 In the case of underwater electrical wire explosion in the microsecond and nanosecond time scales, it was shown that high pressures generated in the surrounding water during the discharge might suppress the generation of the plasma shell. [12][13][14] In these papers, pressure generated by the expanding material of the exploded wire was reported. The estimated velocity of the wire expansion was ϳ10 4 cm/ s and the pressure generated by such a piston was of the order of a few 10 9 Pa. Obviously, at these pressures the problem of water vaporization is automatically abolished since the critical pressure of water is ϳ2.5 ϫ 10 7 Pa.…”
Section: Introductionmentioning
confidence: 97%